AYAT-AYAT CINTA : HEGEMONI, SUBJEKTIVIKASI, DAN BUDAYA MASSA - Ramayda Akmal (Faculty of Humanities, Jember University, 2012)
This article discusses the ideological aspects of the Ayat-Ayat Cinta novel. It is shown that the willingness for hegemony always goes hand in hand with the willingness for obtaining broader readership. Many interests are put in it with an assumption of the dominated subjects growing in number, but at the same time, the offered values have never been fully accepted as the dominating group expects. (Islamic group surrounding Habiburrahman El Shirazy). The text of AAC is full of tension between the two conflicting interests. On one hand, Islam is presented as universal, but on the other hand particular. Islam is also considred complete, but sometime needs the world to perfect itself. This condition is presented in the AAC for a particular reason. Islam-ness in the AAC is Islam that should be accepted by the mass. Islam-ness becomes an economic commodity. Therefore, AAC has to present a dynamic hegemony in which there is negotiation and resistance.Keywords: Islamic novel, ideology, Ayat-Ayat Cinta